Frequency-Based Analysis of Mosque Qibla Errors in Medan - Rakhmadi, Arwin Juli; Putraga, Hariyadi; Ritonga, Marataon; Ismail, Ismail (Fakultas Syari'ah dan Hukum UIN Walisongo, 2025)
Mosque plays a vital role in supporting the performance of prayer comfortably and solemnly. However, one of the most crucial elements in mosque construction is the accuracy of the qibla direction facing the Kaaba. In cities far from the Kaaba, such as Medan, determining the qibla direction cannot be done visually and requires precise astronomical calculations and technical approaches. The problem that arises is the continued presence of mosques with qibla directions deviating from the correct orientation, which can affect the quality of worship for Muslims. This study uses a specially reduced mosque Qibla measurement sample data in Medan city. This paper analyzes data from 38 mosque samples with Qibla direction errors, which were re-measured by the UMSU OIF team. The data were then processed using a frequency distribution method to provide an overview of the error distribution in mosque Qibla directions across the city of Medan. This study found that the error often seen is a deviation of 9-12 degrees from the Qibla direction, and the mistake factors. This study also found that the misalignment of Qibla directions in Medan is mainly due to prioritizing land efficiency over directional accuracy during mosque construction, as well as relying on general assumptions and previously heard fatwas rather than precise astronomical calculations.